Natural Bioactive Molecules as Potential Agents Against SARS-CoV-2 - Chen, Wei; Wang, Zhihao; Wang, Yawen; Li, Yiping (Frontiers in Pharmacology, 2021)
In the past two decades, pandemics of several fatal coronaviruses have posed enormous challenges for public health, including SARS-CoV (2003), MERS-CoV (2012) and SARS-CoV-2 (2019). Among those, SARS-CoV-2 continues to ravage the world today and leads to millions of deaths and incalculable economic damage. Till now, there is still no clinically proven antiviral available drug for SARS-CoV-2. However, in the light of bioactive molecules of natural origin, especially medicinal plants, those excellent resources will provide the potential treatment for SARS-CoV-2. During the battle against coronaviruses, many classes of natural bioactive molecules have proven to be powerful weapons, acting at different stages of the viral life cycle and targeting different viral or host proteins, such as PLpro, 3CLpro, RdRp, helicase, spike, ACE2, and TMPRSS2, etc. Those may provide a viable strategy to develop therapeutic agents. This review presents fundamental biological information of SARS-CoV-2, including the viral biological characteristics and invasion mechanisms. It also summarizes reported natural bioactive molecules with anti-coronavirus properties arranging by their different targets in the life cycle of viral infection of human cells, and discusses the prospect of these bioactive molecules for the treatment of COVID-19.